Kebijakan Hukum Pidana Dalam Penanganan Perkara Pidana Anak di Indonesia - Gilang Kresnanda Annas (UIN Sunan Kalijaga Yogyakarta, 2019)
The birth of Law Number 11 of 2012 concerning theCriminal Justice System for Children (SPPA) brought a breathof fresh air in the development of child criminal law inIndonesia. Therefore Law Number 3 of 1997 concerningJuvenile Court is no longer valid. The Children's JudicialSystem Law currently adopts many international agreementswhich are expected to improve and bring about changes in thehandling of child criminal cases. The policy of penalties in theSPPA Act now pays more attention to the protection of therights of children in conflict with the law at every level ofjustice, one of which is evident from the reduction in the periodof detention of children in the judicial process from 200 days toonly 110 days. In addition, a new policy emerged in the world ofjuvenile justice, namely the concept of diversion and restorativejustice. Diversity and Restorative Justice are policies that canbe taken by law enforcers to shift the process of handlingformal cases to non-formal (without using criminal law). Withdiversion and restotarive justice policies, it is expected to beable to eliminate the adverse effects of children when enteringthe criminal justice process and the perpetrators can realizemistakes, give a sense of suspicion for the actions committedand not repeat their actions